FROM SAMARKAND TO ISTANBUL, OR ALI QUSHCHI AS THE VALUABLE “TROPHY” OF SULTAN MEHMED THE CONQUEROR - Muhammadazimov Abdulbosit Abduvoxid ugli,Jurayev Sherzod Norovich (International Journal of Literature and Language Studies, 2026)
This article examines the life and scientific heritage of Ali Qushji, a major figure of the Timurid Renaissance, astronomer, and mathematician, as well as his role in developing diplomatic and cultural relations between Central Asia and the Ottoman Empire in the 15th century. The relocation to Istanbul of Ali Qushji, a loyal disciple of Ulugh Beg and director of the Samarkand Observatory, not only facilitated the exchange of science between the two regions but also laid the foundation for the formation of the Ottoman observatory and madrasa systems. Based on archival sources and historical data, the paper analyzes the impact of his works, such as "Al-Fathiyya" and "Al-Muhammadiyya," on the global science of that era, as well as how his personality served as a mutual diplomatic bridge between the Timurids and the Ottomans. Furthermore, numerous works of Ali Qushji and the views expressed about him by various scholars are presented.